2014
DOI: 10.1016/j.bjorl.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of nasal shapes and angles in young adults

Abstract: The average values of the nose in this population may be used as a guide to plan corrective esthetic-cosmetic surgery and for burn scars of the nose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 22 publications
4
36
2
1
Order By: Relevance
“…Baykal et al (2014) published a series of 47 patients who presented "hump deformities" and "nasal axis deviations", which were treated with open or closed rhinoplasty; satisfaction from 21% to 72% was observed in the postoperative stage, with significant differences in all the assessments. Studies by Uzun & Ozdemir (2014) also showed similar results.…”
Section: Discussionsupporting
confidence: 65%
“…Baykal et al (2014) published a series of 47 patients who presented "hump deformities" and "nasal axis deviations", which were treated with open or closed rhinoplasty; satisfaction from 21% to 72% was observed in the postoperative stage, with significant differences in all the assessments. Studies by Uzun & Ozdemir (2014) also showed similar results.…”
Section: Discussionsupporting
confidence: 65%
“…Table 3 presents reported results by various authors. Uzun and Ozdemir (2014) reported on NFR, NTA, and NLA of the external nose in Turkish population [8]. Interestingly, their study reported acute values for female NTA, which meant that high proportion of Turkish females have pointed noses.…”
Section: Discussionmentioning
confidence: 98%
“…Minimal variations were observed in relation to NFA and NMA amongst ethnic groups of various studies. However, when it comes to Present study methodology was similar to that adopted by Uzun and associates [8]. However, Eliakim-Ikechukwu et al [9] and Anibor et al [10] also adopted similar methodology, except for the fact that they used lateral photograph printouts and then measured the angles on the hard copies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations